Hybrid Public Sphere in The Digital Era: A Systematic Literature Review from A Habermasian Perspective - Chair Amin; Nur Kholisoh; Leila Mona Ganiem (International Journal Labs, 2026)
The rapid expansion of digital platforms, algorithmic governance, and networked communication has fundamentally transformed the structure of public communication, creating new challenges for understanding democratic deliberation and public participation in contemporary societies. This research aims to systematically examine the evolution of the hybrid public sphere in digital public communication research from a Habermasian perspective, analyse how Habermasian concepts are applied and reinterpreted in digitally mediated environments, and identify emerging opportunities, challenges, and future research directions. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, data were collected from the Scopus database and analysed through thematic synthesis. A total of 28 peer-reviewed articles published between 2010 and 2025 were selected for qualitative analysis. The findings reveal that the hybrid public sphere has evolved into a platformised, networked, and algorithmically mediated communication environment, characterised by the interaction of online and offline communication, social media platforms, civic participation, and digital activism. The reviewed studies confirm the continuing relevance of Habermasian concepts — including the public sphere, communicative action, and deliberative democracy — while also demonstrating their reinterpretation in response to platform capitalism, algorithmic governance, affective publics, and emotional communication. The review further identifies democratic opportunities arising from expanded participation and networked engagement, alongside challenges related to misinformation, polarisation, communicative fragmentation, and platform domination. This study advances Habermasian public sphere theory by synthesising fragmented discussions on hybrid public communication and proposing a platformised, networked, and affective hybrid public sphere, with implications for digital platform governance, democratic communication policy, and civic digital literacy in hybridised ecosystems.